Software Architecture of the Automated Animal Behavior Analysis System - Sinitca, A. M.; Kaplun, D. I.; Kovrigin, V. K.; Zamansky, A. (2019 III International Conference on Control in Technical Systems (CTS), 2019)
One of the most important tools for animal behavior and animal welfare scientists is video-based analysis. Despite the fact that automatic analysis system exists for many species, field of automated video-based behavior analysis doesn't have an effective tool for higher animals, as dogs and therefore scientists have to use manual analysis. This work is aimed at solving this issue by developing automated software. Sleep analysis task used as basic task for development and testing. This paper describes architecture of system for automated analysis of animal behavior.